2009
DOI: 10.1007/s11626-009-9214-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical loading promotes Lewis lung cancer cell growth through periostin

Abstract: Mechanical loading is known to trigger proliferation of tumor cells. Periostin is a new molecule found to increase in many cancers. To determine how mechanical strain modulates tumor growth and its possible mediation by periostin through TGF-beta1, Lewis lung cancer cells were cultured on flexible-bottomed culture plates and cyclically strained using Flexercell Strain Unit. Real-time RT-PCR was used to quantify periostin and TGF-beta1 mRNA levels at 6, 12, 18, and 24 h of loading. In addition, periostin and TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
(18 reference statements)
0
12
0
Order By: Relevance
“…Periostin clearly plays crucial roles in tissue repair. However, in some cases, chronic or superabundant periostin expression can accelerate pathogenesis of tumours (22,23), bronchial asthma (24,25), atopic dermatitis (26,27), polycystic kidney disease, and other fibrotic diseases (28). As recently reported, periostin promotes chronic inflammation by activating nuclear factor kappa B (NF-ĸB) signaling (26,29,30).…”
Section: Discussionmentioning
confidence: 94%
“…Periostin clearly plays crucial roles in tissue repair. However, in some cases, chronic or superabundant periostin expression can accelerate pathogenesis of tumours (22,23), bronchial asthma (24,25), atopic dermatitis (26,27), polycystic kidney disease, and other fibrotic diseases (28). As recently reported, periostin promotes chronic inflammation by activating nuclear factor kappa B (NF-ĸB) signaling (26,29,30).…”
Section: Discussionmentioning
confidence: 94%
“…In summary, these data show that periostin is a prosurvival protein, largely involved in cell response to environmental stress [61,63,68]. By binding to integrins or cell surface receptors, periostin can activate intracellular signaling pathways leading to inhibition of apoptosis through inactivation of caspases 3 and 9 and prosurvival signaling resulting in increased bone formation [12,61,66,73].…”
Section: Periostin Promotes Osteoblast Adhesion Differentiation Andmentioning
confidence: 85%
“…By binding to integrins or cell surface receptors, periostin can activate intracellular signaling pathways leading to inhibition of apoptosis through inactivation of caspases 3 and 9 and prosurvival signaling resulting in increased bone formation [12,61,66,73].…”
Section: Periostin Promotes Osteoblast Adhesion Differentiation Andmentioning
confidence: 99%
“…We previously reported that loading and PTH increases periostin expression in osteocytes [34], and that periostin decreases the expression of apoptotic molecules such as caspase 3 [47], potentially through direct binding to intergrin αVβ5 which activate downstream FAK and Akt pathways. In others tissues, increased periostin expression have also been suggested to represent an adaptative cell response to maintain cell survivals against an environmental stress [69], [70], [71]. Therefore, it is possible that absence of periostin promoted BPs pro-apoptotic effects on osteocytes [61][62], which together with low bone turnover would explain the persistence and accumulation of empty osteocytic lacunae.…”
Section: Discussionmentioning
confidence: 99%